Pendampingan UMKM Emping Melinjo Kalurahan Giriasih Melalui Pembuatan Kemasan dan Legalitas Usaha - Tamzysi, Cholila; Taufiq, Agus (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2025)
The home industry is the backbone of the development of MSMEs in Indonesia which is growing quite rapidly so that it has a positive impact on strengthening the economy, both at the regional and national levels. The production of emping melinjo UMKM has emerged in Giriasih Village, Gunungkidul, the emping melinjo business actors are dominated by housewives with the majority of junior high and high school education levels. The limited ability and minimal knowledge and skills possessed by the emping melinjo business actors in developing the business, the emping melinjo industry which should have been able to become a superior product of local MSMEs, has not been able to develop properly, this is the background to this community service being carried out in Giriasih Village. The goal to be achieved in this community service is to provide assistance to emping melinjo industry actors in making product packaging and managing business legality. The implementation of this community service activity uses stages and methods of service starting from counseling, training and assistance for emping melinjo business actors. The output of this community service includes mandatory outputs in the form of journal article publications and additional outputs in the form of packaging design documents and business legality as well as national seminars on the results of community service.